2009
DOI: 10.1021/ef800808t
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Hydrogen Transfer to Anthracene and Phenanthrene over Pd/C

Abstract: Microwave-assisted hydrogen transfer to anthracene and phenanthrene over Pd/C was investigated under mild conditions. The effects of reaction temperature, initial hydrogen pressure, and reaction time on the reactant conversions and product selectivities were examined. The results show that the hydrogenations of both reactants proceed at much lower temperature and hydrogen pressure under microwave irradiation than those by conventional heating and that related reactions include both mon-and biatomic hydrogen tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…However, better hydrogen transfer properties of the carbon-based catalyst cannot be ruled out. A metal-free AC was shown to be effective in hydrogen transfer to anthracene [11], which is indicative of the fact that carbon supports may promote monoatomic hydrogen transfer, as stated in [12]. The amount of coke deposited on the catalysts was significantly lower for the FCNF-supported ones (0.047 and 0.081 g coke •g cat -1 , compared to 0.284 g coke •g cat -1 for NiMo/Al 2 O 3, as observed in Table 3).…”
Section: >450°c and Asphaltene Conversionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, better hydrogen transfer properties of the carbon-based catalyst cannot be ruled out. A metal-free AC was shown to be effective in hydrogen transfer to anthracene [11], which is indicative of the fact that carbon supports may promote monoatomic hydrogen transfer, as stated in [12]. The amount of coke deposited on the catalysts was significantly lower for the FCNF-supported ones (0.047 and 0.081 g coke •g cat -1 , compared to 0.284 g coke •g cat -1 for NiMo/Al 2 O 3, as observed in Table 3).…”
Section: >450°c and Asphaltene Conversionmentioning
confidence: 79%
“…In addition, some studies indicated higher hydrodesulfurisation (HDS), hydrodenitrogenation (HDN) and hydrodemetallisation (HDM) activity of carbon-supported catalysts compared to those supported on Al 2 O 3 , as reviewed in [10]. This higher activity was attributed to a more efficient activation of metal sites and transfer of hydrogen to reactant molecules [11,12]. Additionally, the lower metal-support interaction compared to typical acid supports such as alumina and zeolites makes a larger fraction of active phase available to the reactants.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18] Literature examples include the utilization of Pd/C, [5][6][7] Pd/SiO 2 , [8] PdEnCat, [9] Pd/glass, [10,11] supported/stabilized Pd nanoparticles, [12] Ni/C, [13] Ni/graphite, [14] Cu/C, [15] and other supported metal species [16] in combination with microwave dielectric heating for achieving highly efficient carbon-carbon and carbonheteroatom bond formation reactions. In addition, several cases of microwave-enhanced hydrogenation reactions involving Pd/C and related supported metal species have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several cases of microwave-enhanced hydrogenation reactions involving Pd/C and related supported metal species have been reported. [17,18] However, the selective heating of metal (or other strongly microwave absorbing) particles under microwave conditions is a rather complex phenomenon depending strongly on the type of support, particle size (surface-to-volume ratio), electromagnetic field strength (power density), and a variety of other factors. [4,19] In heterogeneous gas-phase catalysis, the rationale and advantages of using microwave irradiation to selectively heat the often very strongly microwave absorbing catalyst bed while the reactive gas-being inherently microwave transparent-remains at a lower temperature are reasonably well established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation